Tumor-Treating Field Arrays Do Not Reduce Target Volume Coverage for Glioblastoma Radiation Therapy - Stachelek, Gregory C. (Adv Radiat Oncol, 2019)
PURPOSE: To inform development of procedures for using tumor-treating field arrays (TTFields) during glioblastoma radiation therapy by determining whether the placement and repositioning of arrays affects target volume coverage and cranial skin dose. METHODS AND MATERIALS: Radiation plans from 10 consecutive patients treated for glioblastoma were copied to a cranial phantom and reoptimized for phantom anatomy. Dose distributions were then recalculated on 3 additional computed tomographic scans of the phantom with the TTFields electrode arrays placed over distinct locations on the phantom scalp to compare planning target volume (PTV) coverage and skin dose with and without TTFields in place in varying positions. Percent depth dose curves were also measured for radiation beams passing through the electrodes and compared with commonly used bolus material. RESULTS: The presence of TTFields arrays decreased PTV V97% and D97% by as much as 1.7% and 2.7%, respectively, for a single array position, but this decrease was mitigated by array repositioning. On averaging the 3 array positions, there was no statistically significant difference in any dosimetric parameter of PTV coverage (V95-97%, D95-97%) across all cases compared with no array. Mean increases in skin D1cc and D20cc of 3.1% were calculated for the cohort. Surface dose for TTFields electrodes was less than that with a 5-mm superflab bolus. CONCLUSIONS: Our work demonstrates that placement of TTFields arrays does not significantly affect target volume coverage. We show that repositioning of TTFields arrays, as is required in clinical use, further minimizes any dosimetric changes and eliminates the need for replanning when arrays are moved. A slight, expected bolus effect is observed, but the calculated increases in skin dose are not clinically significant. These data support the development of clinical trials to assess the safety and efficacy of combining concurrent chemoradiotherapy with TTFields therapy for glioblastoma.